The Effect of Honey (Apis Mellifera) Fermentation On Cisplatin Induced Hepatic Histology of Rats and The Review According to Islamic Perspective - Fakhria Mutia; Restu Syamsul Hadi; Firman Arifandi (Junior Medical Journal, 2022)
Background: Cancer is one of the main killer diseases in the world. Cancer must be treated properly. The most common cancer treatment is chemotherapy. Cisplatin is one of the chemotherapy drugs used because of its wide efficacy for the treatment of various types of cancer. Side effects of cisplatin include ototoxicity, nephrotoxicity, hepatotoxicity, neurotoxicity and bone marrow depression. Therefore, there is a need for a solution that can reduce the side effects of cisplatin. One of the natural ingredients that can reduce the side effects of cisplatin is honey. Methods: This research is in the form of primary data, the data is taken directly by conducting an in vivo experiment. This study was divided into 4 groups, namely the untreated group, the cisplatin treatment group only, the cisplatin treatment group with 5% honey fermentation and the cisplatin treatment group with 10% honey fermentation. After that, HE staining was performed to see the histopathological picture of liver cells. Results: Fermentation of honey can reduce the size of congestion and hemorrhage from liver cells exposed to cisplatin. Conclusion: Fermented honey can protect the liver from the toxic effects of cisplatin exposure. In the view of Islam, treatment is one of the efforts in getting the gift of healing from Allah Subhanahu wa Ta'ala. Islam and medicine agree on the importance of this research to support the goals of Islamic law, namely Maqashid Syari'iyah.